2018
DOI: 10.3748/wjg.v24.i39.4462
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of glutathione S transferase family genes in patients with sporadic colorectal cancer

Abstract: AIMTo evaluate the association between polymorphisms in glutathione S transferases (GSTs) and the risk of sporadic colorectal cancer (SCRC), tumor progression and the survival of patients.METHODSA case-control study of 970 individuals from the Brazilian population was conducted (232 individuals from the case group with colorectal cancer and 738 individuals from the control group without a history of cancer). PCR multiplex and PCR-RFLP techniques were used to genotype the GST polymorphisms. The tumors were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
2
10
1
Order By: Relevance
“…The present study confirmed data from the literature, that report the predominance of cases between the fourth and sixth decade of life, and that smoking and alcohol consumption is strongly related to increased risk of developing this type of cancer (Choudhury et al, 2015;Rodrigues-Fleming et al, 2018). The studies carried out in Northeastern Brazil evidenced increased risk of oral cancer in patients presenting smoking and alcohol consumption synergism compared to non-synergetic consumption of cigarettes and alcohol (Andrade et al, 2015;Dias et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The present study confirmed data from the literature, that report the predominance of cases between the fourth and sixth decade of life, and that smoking and alcohol consumption is strongly related to increased risk of developing this type of cancer (Choudhury et al, 2015;Rodrigues-Fleming et al, 2018). The studies carried out in Northeastern Brazil evidenced increased risk of oral cancer in patients presenting smoking and alcohol consumption synergism compared to non-synergetic consumption of cigarettes and alcohol (Andrade et al, 2015;Dias et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Sixty-three articles of sixy-four case–control studies [ 15–17 , 19 , 21–24 , 26 , 27 , 30 , 31 , 33 , 34 , 36 , 38–42 , 45 , 47 , 48–52 , 54–58 , 62–64 , 67–70 , 73 , 74 , 76–78 , 80–82 , 87–90 , 93 , 96–99 , 102 , 105 , 109 , 111–114 ] were eligible concerning the GSTT1 present/null polymorphism (19,725 cases and 28,725 controls; 34 studies on Caucasians, 23 on Asians, one on Indians, one on Africans, and five on mixed populations) with CRC risk. Thirty-two publications of thirty-three case–control studies [ 15 , 19 , 22–24 , 27 , 31 , 33 , 38 , 39 , 41 , 42 , 45 , 49 , 52 , 55–57 , 63 , 67 , 68 , 70 , 76–78 , 90 , 96 , 97 , 99 , 105 , 109 , 112 ] were included regarding their combined effects (8270 cases and 14,381 controls; 11 studies on Caucasians, 17 on Asians, one on Indians, one on Africans, and three on mixed populations) with CRC risk. Fifty-five studies had a quality score ≥ 6 and the remaining 31 had a quality score < 6 regarding the GSTM1 present/null polymorphism; 48 high-quality studies were examined and the remaining 16 were low-quality concerning the GSTT1 present/null polymorphism; a total of 25 high-quality and eight low-quality studies were included on their combined effects with CRC risk.…”
Section: Resultsmentioning
confidence: 99%
“…According to research, the polymorphism of GST genes may influence the risk of developing T2D, as well as its course, complications and treatment effectiveness [9,10]. Similar observations were made for CDC, where the GST genotype may be a factor modifying the risk of disease development and progression [7,11,12].…”
Section: Introductionmentioning
confidence: 84%